The Impact of Empathy on Leadership Effectiveness among Business Leaders in the United States and Malaysia - A., Wan Abdul Rahman, W.; Castelli, Patricia Ann (International Journal of Economics, Business and Management Studies, 2013)
Global markets have increased the challenges faced by business organizations causing them to manage their employees across varying cultures, different time zones, and complex organizational structures. Thus, more effective leadership skills are required to enhance business survival and continuity. Empathy is a pivotal leadership tool in today’s global market. This study investigated the impact of empathy on leadership effectiveness by testing four hypotheses to determine the relationships between empathy, leadership effectiveness, and leaders’ backgrounds using a sample of 216 business leaders located in the United States (51.9%) and Malaysia (48.1%). Davis’s Interpersonal Reactivity Index (IRI) was used to measure empathy and to test the impact of empathy on leadership effectiveness in the United States and Malaysia. The results indicate that American business leaders have significantly higher empathy than Malaysian business leaders, and that leaders with higher empathy appear to be more effective. The clear implication is that multinational organizations need to develop leaders with high empathy skills.